The effectiveness of emotion-focused therapy on anxiety sensitivity, distress tolerance and coping strategies in betrayed women - Naderian , Mohammadreza; Amini , Masoumeh; Karimi , Maryam; Rezaei , Shahrzad (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: This study aimed to investigate the effectiveness of emotion-focused therapy on anxiety sensitivity, distress tolerance, and coping strategies in betrayed women.Method: The current research method was quasi-experimental, with a pre-test-post-test-follow-up design with a control group. The statistical population included all women affected by extramarital relationships who had been referred to psychological clinics and specialized marriage centers (under the welfare organization) in Isfahan City in order to use psychological services in the second half of 2022. The sample of this research included 30 women affected by extramarital relationships who were willing to participate in the research and were selected as available sampling. The data were obtained by using an anxiety sensitivity questionnaire (2005), a distress tolerance scale (2005), and a coping strategies questionnaire (1984). The experimental group underwent Johnson's (2004) emotion-focused treatment. The data obtained from the research were analyzed using SPSS version 26 and the statistical method of analysis of covariance.Results: The results showed that emotion-focused therapy was effective in anxiety sensitivity (F=22.94, P<0.001), distress tolerance (F=29.17, P<0.001), and problem-oriented (F=8.95, P<0.001) and emotion-oriented (F=18.47, P<0.001) coping strategies in betrayed women.Conclusion: It can be concluded that emotion-focused therapy was effective in anxiety sensitivity, distress tolerance, and coping strategies in betrayed women, and emotion-focused therapy can reduce the problems of betrayed women.